2004
DOI: 10.1534/genetics.166.2.901
|View full text |Cite
|
Sign up to set email alerts
|

A New Deletion of the Mouse Y Chromosome Long Arm Associated With the Loss ofSstyExpression, Abnormal Sperm Development and Sterility

Abstract: The mouse Y chromosome carries 10 distinct genes or gene families that have open reading frames suggestive of retained functionality; it has been assumed that many of these function in spermatogenesis. However, we have recently shown that only two Y genes, the testis determinant Sry and the translation initiation factor Eif2s3y, are essential for spermatogenesis to proceed to the round spermatid stage. Thus, any further substantive mouse Y-gene functions in spermatogenesis are likely to be during sperm differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
103
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(111 citation statements)
references
References 46 publications
8
103
0
Order By: Relevance
“…2 A). These stages contain round spermatids (21), and our findings are in accordance with those of previous studies showing that Ssty, Sly, and Slx transcripts are present only during spermatogenesis, predominantly in round spermatids (2,20,22,23). Importantly, the Hsf2 expression coincided with transcription of the multicopy genes in stages containing round spermatids (II-VIII) (Fig.…”
Section: Hsf2 Functions As a Transcriptional Regulator Of Ssty2 Slysupporting
confidence: 92%
See 3 more Smart Citations
“…2 A). These stages contain round spermatids (21), and our findings are in accordance with those of previous studies showing that Ssty, Sly, and Slx transcripts are present only during spermatogenesis, predominantly in round spermatids (2,20,22,23). Importantly, the Hsf2 expression coincided with transcription of the multicopy genes in stages containing round spermatids (II-VIII) (Fig.…”
Section: Hsf2 Functions As a Transcriptional Regulator Of Ssty2 Slysupporting
confidence: 92%
“…3B). Our results show that in addition to the similar alterations in Ssty2, Sly, and Slx expression, the Hsf2 Ϫ/Ϫ head abnormalities were equivalent to the flattened sperm head phenotype of the XY RIII qdel mutant (23,25,26). The Hsf2 Ϫ/Ϫ sperm head anomaly (Fig.…”
Section: Hsf2 ؊/؊ Mice Display Increased Sperm Head Abnormalities Imsupporting
confidence: 67%
See 2 more Smart Citations
“…Interestingly, some of its target genes (Ssty2 and Sly) are part of multi-copy gene clusters in the malespecific region of the long arm of the mouse Y chromosome (MSYq) that are expressed exclusively during spermatogenesis. Previous studies have shown that deletion of the MSYq region results in sperm head defects and impaired fertility in mice (Toure et al 2004). Likewise, Hsf2 mutant mice are hypofertile and have a high proportion of sperm with head defects.…”
Section: Dna-binding Proteins That Regulate Spermatogenesismentioning
confidence: 98%